2019
DOI: 10.1016/j.jprot.2019.103416
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic remodeling of the interactomes of Nematostella vectensis Hsp70 isoforms under heat shock

Abstract: Heat shock protein 70s (Hsp70s) are a highly conserved class of molecular chaperones that fold a large proportion of the proteome. Nematostella vectensis (Nv) is an estuarine sea anemone that has emerged as a model species to characterize molecular responses to physiological stressors due to its exposure to diverse, extreme abiotic conditions. Previous transcriptional data has shown dramatic differences among expression profiles of three NvHsp70 isoforms (NvHsp70A, B and D) under stress but it is unknown if, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…However, the accumulated studies have revealed the diversity of HSP70s. It has been demonstrated that different HSP70 isoforms have unique cochaperone and client interactors, and functional diversity is defined by the affinities for specific cochaperones [ 37 , 38 , 39 ]. Together, our discoveries may offer novel clues to explore the relationships between HSP70 family members and uncover the underlying mechanism of HSP70s in contributing to oogenesis, embryogenesis, and the thermal tolerance of eggs.…”
Section: Discussionmentioning
confidence: 99%
“…However, the accumulated studies have revealed the diversity of HSP70s. It has been demonstrated that different HSP70 isoforms have unique cochaperone and client interactors, and functional diversity is defined by the affinities for specific cochaperones [ 37 , 38 , 39 ]. Together, our discoveries may offer novel clues to explore the relationships between HSP70 family members and uncover the underlying mechanism of HSP70s in contributing to oogenesis, embryogenesis, and the thermal tolerance of eggs.…”
Section: Discussionmentioning
confidence: 99%
“…These isoforms appear to have high functional overlap, especially as yeast can maintain viability upon loss of any three Ssa isoforms 24 . Recent evidence suggests that these Hsp70 isoforms are not fully redundant and have specialized roles dictated though unique clientomes 24,57,58 . Although 3 of 4 lysines are conserved in the Ssa proteins, the heat inducible Ssa3 and Ssa4 contain an alanine at position 562 instead of lysine, and thus cannot undergo acetylation at this site.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, NvHsp70D interacted with a total of 639 (55%), of which 38 (3%) were unique to the D isoform. NvHsp70A and NvHsp70B shared 240 interactors (21%), whereas NvHsp70A and NvHsp70D only shared 21 interactors (1.8%) and NvHsp70B and NvHsp70D 31 interactors [1].…”
Section: Datamentioning
confidence: 99%